Design Aspects of Steep Channel of Chute Spillway - Sharma, T.C.; Rastogi, R.A. (Journal of Soil and Water Conservation, 2022)
Chute may be defined as narrow trough like steep channel in which flow has supercritical velocities. They usually consist of an inlet, steep channel and outlet. The major part of drop in water surface takes place in steep channel. Flow passes through the inlet and down a paved, steeply sloped channel to the floor of outlet. These chutes are commonly used for controlling the steep grades and stabilising gully heads or overfalls. They also find their application for conveying the runoff water down the steep risers in between two consecutive benches in bench terraced land. They are some times also used as emergency and main spillway for small earthen dams so that water may be dropped far- ther than is feasible with drop stuctures. It is well established fact that for larger falls i.e. more than three meters, chutes can be economically constructed as compared to drops, if suitable gro und slopes and soil conditions prevail.